Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content: 1. Hajib bin Zarara Al-Tamimi and his intellectual contributions before Islam Mr. Barka Abdoulaye Abdelhadi , Prof. Ousmane Mahamat Adam , Dr. Mouhamadou Chouibou 2. Ibn Malik’s Approach in Presenting Syntactic and Morphological Judgements; A study in Alfiyah Mrs. Shahd Sabir Toukhi, Dr. Hanan Ahmed Al-Rajhi 3. The importance of justifications and their impact on building the grammatical rule Dr. Siham Youisf Keadan 4. Referencing Words in Surah Al-Nabba: Linguistic Study in Light of Text Linguistics Asst-Prof. Omraan Mohamad Abdulrazak, Co-Prof. Mahmmud Hussein Al-Azazmeh 5. Description of Development in Andalusian Poetry "The Palaces of the Kings of the Taifas" Artistic Study Mr. Mutair Eid M. Alatawi 6. The Image of Horse in Antara Poetry Mr. Khadir Ali Bsharat 7. The birth of Arabic Grammar and Its Origins Dr. Sounia Mohammad Altwassi